Rondas y canciones en el desarrollo cognitivo de los niños de educación inicial, de 4 a 5 años de edad de la Unidad Educativa Francisco Huerta Rendón Ciudad, Babahoyo Provincia Los Ríos - León Astudillo, Angeline Lissett (2023)
The case study was carried out at the Francisco Huerta Rendón Educational Unit in the city of Babahoyo with the objective of analyzing the incidence of rounds and songs on the cognitive development of 4 and 5 year old children. The methodology used consisted of a mixed approach, field and documentary research, inductive method, interview and observation technique with their respective instruments, which were directed at a sample of 30 children and 2 early education teachers. The results were that most children are still in the process of achieving their cognitive development because it is difficult for them to easily memorize nursery rhymes, repeat nursery rhymes with melody, and structure small sentences with proper word order. The teachers consider that the benefits of rounds and nursery rhymes for children are socialization, teamwork, expression of emotions, memorizing, improving language and sharing. Early education teachers consider that they rarely develop rounds and children's songs within the classes and that the main drawbacks in the development of rounds and children's songs is keeping the children focused on the activities and behavior of the students. . In conclusion, rounds and songs are essential for cognitive development, since they promote memory, language and concentration. The songs that the teachers use are: cuckoo the frog sang, an elephant swayed, the frog dance and below it a button.